Annual and interannual variations of the Western Pacific Warm Pool volume and sources of warm water revealed by Argo data - Wu, XiaoFen; Zhang, QiLong; Liu, ZengHong (Science China. Earth sciences, 2014)
Based on gridded Argo profile data from January 2004 to December 2010, together with the P-vector inverse method, the three-dimensional structure, annual and inter-annual variations in volume of the Western Pacific Warm Pool （WPWP） are studied. The variations of latitudinal and longitudinal warm water flowing into and out of the WPWP and the probable mecha- nism of warm water maintenance are also discussed. From the surface to the bottom, climatic WPWP tilts southward and its area decreases. The maximum depth could extend to 120 m, such that its volume could attain 1.86x10~5 m3. Annual variation of the WPWP volume shows two obvious peaks that occur in June and October, whereas its inter-annual variations are related to ENSO events. Based on a climatic perspective, the warm water flowing latitudinally into the pool is about 52 Sv, which is mainly through upper layers and via the eastern boundary. Latitudinally, warm water flowing outward is about 49 Sv, and this is mainly through lower layers and via the western boundary. In contrast, along the latitude, warm water flowing into and out of the pool is about 28 Sv and 23 Sv, respectively. Annual and inter-annual variations of the net transportation of the warm water demonstrate that the WPWP mainly loses warm water in the west-east direction, whereas it receives warm water from the north-south direction. The annual variation of the volume of WPWP is highly related to the annual variation of the net warm water transportation, however, they are not closely related on inter-annual time scale. On the inter-annual time scale, in- fluences of ENSO events on the net warm water transportation in the north-south direction are much more than that in the west-east direction. Although there are some limitations and simplifications when using the P-vector method, it could still help improve our understanding of the WPWP, especially regarding the sources of the warm water.